Known and Respected, but not too much: The Cappadocian Fathers and the Apocrypha - Leemans, Johan (Ephemerides theologicae Lovanienses, 2024)
In Late Antiquity, apocryphal writings circulated widely. This article offers a case study on how the leaders of mainstream Christianity used and viewed these writings. I provide a survey of all relevant material in the works of the Cappadocian Fathers, Amphilochius of Iconium, and Asterius of Amasea, focusing on the Protoevangelium of James, Thecla of Iconium, the Ascension (Martyrdom) of Isaiah, the Acta Petri, and 4 Maccabees. The analysis shows that these mainstream Christian leaders were familiar with these writings, their storylines, and main characters, but, with few exceptions, only in general terms. They used them sparingly and mostly in their sermons, never in their theological writings proper. They did not reject these apocrypha and drew freely from them but did so without encouraging their congregations to engage with them in the same way. In sum, these late antique bishops lived in more than one world at the same time: as theologians, they did not rely on these apocryphal writings, but when addressing a broader audience, they occasionally referred to them. After all, these were stories their audiences were familiar with and characters that populated their mental world.